Girl-Child Education and Sustainable National Development through Research and Innovation - Amanze, Samuel U.; Uwanna, Ngozi C. (NIU Journal of Humanities, 2019)
The wide imbalance between the education of men and their women counterpart in various fields of learning has had out-cries from various quarters and has made the education of the girl-child a very serious issue in the education sector in Nigeria, Africa, and globally. Governments, non-governmental organizations, education planners, mangers and other well-meaning citizens, are burdened on how to reduce this imbalance as they become aware of the enormous contributions women can make in nation building through research and innovation. There are obvious indications that Nigeria’s quest for national development through research and innovation will not be realized until, as a nation, we recognize, appreciate and begin to involve women in national developmental projects. The paper is exploratory and has critically examined the factors militating against the education of the girl-child, proffered practical solutions that addressed this malaise and examined the role of women in sustainable nation building efforts through research and innovation. The paper noted ignorance on the part of parents, the girl-child and men, culture and tradition, insensitivity on the part of government and inadequate enlightenment as some of the problems militating against the girl-child education in Nigeria. Other factors include male dominance in positions of policy formulation and implementation and failure on the part of various governments in protecting the rights of women in matters dealing with the rights of women. The paper therefore recommended a massive campaign by government, voluntary agencies and all for the education of the girl-child, government should, as a matter of urgency, enact policies or re-enforce the existing policies that will encourage the education of the girl-child in Nigeria. Through seminars and workshops at the grass- root parents should be encouraged to send their daughters to school and inform them of the dangers of early marriages and the benefits that will accrue to the family and the nation as a whole when these girls are educated. The culture of early marriage should be discouraged and disbanded. Keywords: Sustainable national development, girl-child, education, research and innovation,